2021
DOI: 10.3390/cancers13112554
|View full text |Cite
|
Sign up to set email alerts
|

2-[18F]FDG PET/CT as a Predictor of Microvascular Invasion and High Histological Grade in Patients with Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) generally presents a low avidity for 2-deoxy-2-[18F]fluoro-d-glucose (FDG) in PET/CT although an increased FDG uptake seems to relate to more aggressive biological factors. To define the prognostic value of PET/CT with FDG in patients with an HCC scheduled for a tumor resection, forty-one patients were prospectively studied. The histological factors of a poor prognosis were determined and FDG uptake in the HCC lesions was analyzed semi-quantitatively (lean body mass-corrected sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
1
7
1
Order By: Relevance
“…been reported in 29% of HCCs with a size ranging from 2 to 5 cm (34). Sabaté-Llobera et al reported that the ratios of well-to less differentiated tumors ranged from 1.3 in the 18F-FDG-positive group to 5.7 in the 18F-FDG-negative group (31). However, nearly 50% of 18F-FDG-positive cases in the present study were well-differentiated HCC.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…been reported in 29% of HCCs with a size ranging from 2 to 5 cm (34). Sabaté-Llobera et al reported that the ratios of well-to less differentiated tumors ranged from 1.3 in the 18F-FDG-positive group to 5.7 in the 18F-FDG-negative group (31). However, nearly 50% of 18F-FDG-positive cases in the present study were well-differentiated HCC.…”
Section: Discussioncontrasting
confidence: 49%
“…Although an extensive review by Gouw et al showed that high-grade tumors but also tumor size and number of nodules to be predictive of MVI ( 33 ), MVI has also been reported in 29% of HCCs with a size ranging from 2 to 5 cm ( 34 ). Sabaté-Llobera et al reported that the ratios of well- to less differentiated tumors ranged from 1.3 in the 18F-FDG-positive group to 5.7 in the 18F-FDG-negative group ( 31 ). However, nearly 50% of 18F-FDG-positive cases in the present study were well-differentiated HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…suggested that the size and number of tumors were important markers for predicting vascular invasion [32]. It has been recognized that poor differentiation of tumor is closely related to metastasis and invasiveness of tumor [33]. Therefore, early rHCC is more likely to recur than late rHCC [9,29], and it is accompanied by multiple hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, β-2-[18F] fluoro-2-deoxy-D-glucose positron emission tomography with computed tomography ( 18 F-FDG PET/CT) has shown to be a valuable molecular imaging tool when evaluating the biological behavior of tumors (11)(12)(13). The FDG uptake in HCC lesions is reportedly associated with more aggressive characteristics, such as a higher histological grade, the presence of microvascular invasion (MVI), early recurrence, and poor overall survival (14)(15)(16). Thus, we aimed to evaluate the potential to use tumor FDG metabolism as an imaging indicator to preoperatively predict the MTM subtype in HCC patients.…”
Section: Introductionmentioning
confidence: 99%